"Is That A Method of Birth Control?" A Qualitative Exploration of Young Women's Use of Withdrawal. Issue 4 (3rd May 2016) - Arteaga, Stephanie; Gomez, Anu Manchikanti
Abstract : Despite its ubiquity, withdrawal is understudied as a family planning method. We investigated the context of and decision making around withdrawal use, drawing on in-depth, qualitative interviews with 38 Black and Latina women (ages 18 to 24). We examined contraceptive use histories to understand when and why participants used withdrawal. The majority of participants ( n = 29; 76%) had used withdrawal in their lifetimes, though two-thirds of users mentioned withdrawal in their contraceptive histories only after interviewer prompts. Withdrawal was primarily used during transitions between contraceptive methods and when other methods were not desired. Relationship context was also an important factor, as many used withdrawal to increase intimacy with their partners; because they felt condoms were no longer necessary due to monogamy; or to fulfill their partners' preferences to increase sexual pleasure. Our findings indicate that decision making around withdrawal is embedded in situational and relational contexts. Future research should explore how health care providers and sex educators can engage young women in discussions of withdrawal's benefits and constraints. A harm reduction framework, which recognizes that optimal use of withdrawal is preferable to not using a pregnancy prevention method at all, may inform the ways that withdrawal can be addressed in clinical and educational settings.